2004
DOI: 10.1126/science.1093360
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Inhibition of Dopamine Neurons in the Ventral Tegmental Area by Aversive Stimuli

Abstract: Dopamine neurons play a key role in reward-related behaviors. Reward coding theories predict that dopamine neurons will be inhibited by or will not respond to aversive stimuli. Paradoxically, between 3 and 49% of presumed dopamine neurons are excited by aversive stimuli. We found that, in the ventral tegmental area of anesthetized rats, the population of presumed dopamine neurons that are excited by aversive stimuli is actually not dopaminergic. The identified dopamine neurons were inhibited by the aversive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
609
4
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(650 citation statements)
references
References 25 publications
(31 reference statements)
36
609
4
1
Order By: Relevance
“…Indeed, whereas 5-HT inhibits DA release (Kapur & Remington, 1996; potentially via 5-HT receptors in DA cells, Nocjar, Roth, & Pehek, 2002), there is no reciprocal relationship for DA onto 5-HT (Adell & Artigas, 1999). Finally, although DA dips have been repeatedly observed when outcomes are worse than expected (e.g., Bayer & Glimcher, 2005;Hollerman & Schultz, 1998;Morris, Arkadir, Nevet, Vaadia, & Bergman, 2004;Satoh et al, 2003;Schultz, 1999;Ungless, Magill, & Bolam, 2004), the predicted phasic increase in 5-HT during these negative prediction errors has yet to be observed (see Daw et al, 2002), and if it is observed, it is unclear how it would preferentially bias no-go learning in the BG.…”
Section: Model Limitations and Further Neurobiological Considerationsmentioning
confidence: 99%
“…Indeed, whereas 5-HT inhibits DA release (Kapur & Remington, 1996; potentially via 5-HT receptors in DA cells, Nocjar, Roth, & Pehek, 2002), there is no reciprocal relationship for DA onto 5-HT (Adell & Artigas, 1999). Finally, although DA dips have been repeatedly observed when outcomes are worse than expected (e.g., Bayer & Glimcher, 2005;Hollerman & Schultz, 1998;Morris, Arkadir, Nevet, Vaadia, & Bergman, 2004;Satoh et al, 2003;Schultz, 1999;Ungless, Magill, & Bolam, 2004), the predicted phasic increase in 5-HT during these negative prediction errors has yet to be observed (see Daw et al, 2002), and if it is observed, it is unclear how it would preferentially bias no-go learning in the BG.…”
Section: Model Limitations and Further Neurobiological Considerationsmentioning
confidence: 99%
“…Presumed dopamine neurons were found 7.5-8.5 mm from the brain surface and were recognized by their characteristic triphasic action potential waveform of more than 2.0 ms duration, basal firing rates of 1-10 Hz, and frequent occurrence of burst firing (Wang, 1981). Moreover, the 'Ungless-filter', consisting of tail-or toe-pinch, was applied and only cells that responded with a transient inhibition of firing were included in the study (Ungless et al, 2004). Extracellular electrical activity was amplified, filtered (band pass 0.3-3 kHz), discriminated, and monitored on an oscilloscope (TDS 310, Tektronix, Beaverton, OR) and an audiomonitor (Grass, AM8B/C, West Warwick, RI).…”
Section: Extracellular Single Cell Recording Of Dopaminergic Neurons mentioning
confidence: 99%
“…1), where the fast-firing mesocortical cells are preferentially located (Chiodo et al 1984). However, several recent studies questioned the traditional criteria of indirect DA cell identification as less reliable and absolute than was originally thought (Ungless et al, 2004;Margolis et al, 2006). Using Neurobiotin staining with subsequent histochemical identification of the recorded cells in anesthetized conditions, Ungless et al (2004) showed that not all VTA cells with long, triphasic cells (10/18) are DA-containing, although they found that spike duration is relatively longer in identified DA cells compared to non-DA neurons.…”
Section: Vta Cell Heterogeneity and The Issue Of Neuronal Phenotypementioning
confidence: 99%
“…However, several recent studies questioned the traditional criteria of indirect DA cell identification as less reliable and absolute than was originally thought (Ungless et al, 2004;Margolis et al, 2006). Using Neurobiotin staining with subsequent histochemical identification of the recorded cells in anesthetized conditions, Ungless et al (2004) showed that not all VTA cells with long, triphasic cells (10/18) are DA-containing, although they found that spike duration is relatively longer in identified DA cells compared to non-DA neurons. Therefore, conservatively we can assume that some LS VTA cells recorded in this study could be non-DA cells and such a possibility has been suggested in our previous work (Kiyatkin and Rebec, 1998).…”
Section: Vta Cell Heterogeneity and The Issue Of Neuronal Phenotypementioning
confidence: 99%
See 1 more Smart Citation